2019
DOI: 10.1093/heapol/czz059
|View full text |Cite
|
Sign up to set email alerts
|

Access to healthcare for children with Congenital Zika Syndrome in Brazil: perspectives of mothers and health professionals

Abstract: The Congenital Zika Syndrome (CZS) epidemic took place in Brazil between 2015 and 2017 and led to the emergence of at least 3194 children born with CZS. We explored access to healthcare services and activities in the Unified Health Service (Sistema Único de Saúde: SUS) from the perspective of mothers of children with CZS and professionals in the Public Healthcare Network. We carried out a qualitative, exploratory study, using semi-structured interviews, in two Brazilian states—Pernambuco, which was the epicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
17

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 33 publications
1
42
0
17
Order By: Relevance
“…While adequate access to health care is an important issue in Brazil, particularly for families affected by CZS ( Albuquerque et al , 2019 ), this article contributes to this discussion of the importance of a trust-based healthcare system for cooperation between healthcare workers and caregivers. Health systems are inherently relational, and many of its challenges lie in its behavioural and relationship dynamics ( Gilson, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
“…While adequate access to health care is an important issue in Brazil, particularly for families affected by CZS ( Albuquerque et al , 2019 ), this article contributes to this discussion of the importance of a trust-based healthcare system for cooperation between healthcare workers and caregivers. Health systems are inherently relational, and many of its challenges lie in its behavioural and relationship dynamics ( Gilson, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
“…This has been highlighted in other studies. 35 Furthermore, lack of access to services (mainly due to distance, cost and lack of availability) was a massive issue for families of children with CZS. 36 From our study, it is clear that services for support and rehabilitation in a single location would minimise problems of low attendance and/or avoidance of services.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that problems of caregivers were compounded by difficulties seeking care and lack of coordination of services, as well as gaps in the knowledge of healthcare providers. 25 We demonstrated that there are high costs incurred, both on the side of the affected families and the healthcare system, which had potentially large financial impacts (paper in submission). This information is critical to improving services to better support the affected children and their families, and prior to our study was assumed but not documented systematically.…”
Section: Collaboration Between Brazilian and Uk Researchersmentioning
confidence: 95%